Analysis of Hydrological Characteristics of River, Canal, and Lake: A Case Study Sun Ye In –Se Gon Area Sint Gaing and Kyaukse Townships, Mandalay Region - Kay Thi Khaing; Zin Hein Hlaing; Sitt Marn; Htet Wai Phyoe; Thet Han Oo; Zaw Min Aung; Nyein Khant Kyaw; Ye Thiha (CV. Literasi Indonesia, 2025)
Among the most significant branches of the Zawgyi River (ZGR) are the Thindwe dam (TDD), Thindwe canal (TDC), and Sun Ye In (SYI), all of which are known to be impacted by household and agricultural pollution. In this study, many physicochemical parameters (temperature, conductivity, salinity, TDS, pH, and ORP) were measured to assess the water quality of ZGR, TDD, TDC, and SYI. Between March 2024 and March 2025, water samples were taken from ZGR, which is situated at the bottom of SYI Lake, on average, ten times per month. All experimental data were gathered in the field and assessed as drinking water based on WHO (World Health Organization) and EC (European Communities) standards. The surface water's pH, temperature, ORP, TDS, and EC were distributed spatially. ArcGIS 10.7 was used to identify the seasons based on the water quality by using the spatial distribution of pH, temperature, ORP, TDS, and EC in the surface water. Additionally, TDS and EC accumulations in TDC water were found to be significantly greater than drinking water limitations.